Job Stress and Lecturers’ Efficiency In Obafemi Awolowo University, Ile-Ife, Nigeria - Timothy Olugbenga AJADI (Revista de Știinţe Educaţiei)
The roles of lecturers in universities cannot be underestimated. This is because lecturers are the bones who interpret the content of the curriculum. Hence, lecturers are expected to be efficient. This study however investigated job stress and lecturers’ efficiency in Obafemi Awolowo University, Ile Ife, Nigeria. The population of the study comprised all academic staff in all the 10 Faculties and two Colleges of the University. A sample of 50 participants was selected from each of the five purposively selected faculties. An adapted questionnaire titled titled ‘Job Stress and Lecturers’ Efficiency (JSLEQ) was used to collect information from the respondents. The instrument was validated and trial tested on population outside the sample. The reliability index of the instrument was 0.91 using Crobatch Alpha method of analysis. Descriptive and inferential statistics were used to answer the research question and test the hypothesis respectively. The results showed that anxiety was the most prominent stress of the six-stress found among lecturers in OAU and that stress has significant influence on lecturers’ efficiency in Obafemi Awolowo University, Ile-Ife, Nigeria. The study recommends employment of seasoned counsellors and equipping the counselling unit with 21st century equipment that can be used to manage anxiety among the entire workers in the university.